y= 7+x
3x-(7+x)= -15
3x-7-x= -15
2x= -8
x= -4
y-(-4)=7
y+4=7
y=3
(-4,3)
2006-11-18 08:46:49
·
answer #1
·
answered by 7
·
0⤊
0⤋
3x - y = -15 .............. (1)
y - x = 7
so y = 7 + x ............. (2)
Substitute equation (2) into equation (1)
Therefore 3x - (7 + x) = -15
2x - 7 = -15
2x = -8
x = -4
Substitute in equation (2)
y - -4 = 7
ie y + 4 = 7
So y = 3
Check in equation (2)
3x - y = 3 * (-4) - 3
= -12 - 3
= -15 ..... YESSSSSSSSSSSSSS!!!!!
So the solution is x = -4 y = 3
2006-11-18 08:47:25
·
answer #2
·
answered by Wal C 6
·
0⤊
0⤋
3x-y=-15 eq.1
y-x=7 eq.2
y=7+x eq.3
from equation 1 substitute the value of y taken from equation 2
3x-y=-15
3x-(7+x)=-15
3x-7-x= -15
3x-x-7= -15
2x=-15+7
2x=-8
x=-8/2
x=-4
from equation 3 substitute the value of x
y=7+x
y=7+(-4)
y=7-4
y=3
checking:
3x-y=-15
3(-4)-(3)=-15
-12-3=-15
-15=-15
2006-11-18 09:06:50
·
answer #3
·
answered by liendy_13 1
·
0⤊
0⤋
3x - y = -15.....Eq 1
y - x = 7.....Eq 2
Consider Eq 2
y - x = 7
y = x + 7
Now substitute the derived value of 'y' in Eq 1
3x - y = -15
3x -(x + 7) = -15
3x - x - 7 = -15
2x - 7 = -15
2x = 7 - 15
2x = -8
x = -8/2
x = -4
Substitute the value of 'x' in Eq 2
y - x = 7
y -(-4) = 7
y + 4 = 7
y = 7-4
y = 3
2006-11-18 14:28:35
·
answer #4
·
answered by Akilesh - Internet Undertaker 7
·
0⤊
0⤋
Add x to both sides of the second equation to get:
y=x+7.
Then, instead of y, have (x+7), substitute it in to get:
3x-(x+7)=-15
Then remove the parenthesis (really distributing a -1)
3x-x-7=-15
Then, combine the like terms:
2x-7=-15
Then, add 7 to both sides to get:
2x=-8
Divide both sides by 2 to isolate the variable and you're left with:
x=-4
-----------------------------------------------------------------------------------
Then, solve for y:
substitute in x=-4 in the second equation to find y:
y-(-4)=7
Remove double negative:
y+4=7
Subtract 4 from both sides to isolate y:
y=3
Hope this helps!!
2006-11-18 10:14:02
·
answer #5
·
answered by quickster94 3
·
0⤊
0⤋
take the easies question and rearrange it to solve for one variable. in this case i would take y - x = 7 and re arrange it to read y = x + 7. Now take that equation and substitute it into the other one where you see a y
3x - (x +7) = -15
3x - x= 2x, -15 - 7 = -22
so now your equation looks something like y = 2x - 22
now solve for x, then take either equation and solve for y, and then you have your answer
2006-11-18 08:55:40
·
answer #6
·
answered by mcdonaldcj 6
·
0⤊
0⤋
y-x=7
y=x+7
3x-(x+7)= -15
3x-x-7= -15
2x-7= -15
2x= -8
x= -4
y-(-4)=7
y+4=7
y=3
2006-11-18 08:53:17
·
answer #7
·
answered by chrisjptine 1
·
0⤊
0⤋